(3ebOeI aj EOGQI GdEfJGL hGdYedjGJs - (3eMeO GdMSjf(B, (3HOjhjs ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2004)
(3ebOeI aj GOGQI GdGfJGL,fXGe eYdheGJ GdGfJGL,GNJHGQ ehbY GdeTQhY,GdJQJjH GdOGNdj ddeTQhY,OQGSI GdMQcI hGdhbJ,GOGQI GdGfJGLjI,GdWGbI GdGfJGLjI,GOGQI GdLhOI GdTGedI(B.s
(3GdeQGLY U(B. 195s
Keywords: (3EOGQI GdEfJGLs; (3GdLhOI GdTGedIs